2007
DOI: 10.1109/tasc.2007.899683
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Thermal Characteristics of a Model Dipole Magnet for the SIS 300

Abstract: The synchrotron SIS 300, developed for the Facility for Antiproton an Ion Research (FAIR) project at GSI, will use fast-cycling dipoles with 100 mm inner diameter coils, magnetic field amplitude of 6 T and a ramp rate of 1 T/s. This work presents the calculations of the magnetic and thermal characteristics of a 1 m model dipole with optimized 2D and 3D geometries. AC losses in the coil and iron yoke, as well as temperature margins, were analyzed. Production tolerances for the main geometrical parameters were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The comparison between designs of the old geometry [10] (marked by the index o) and the new alternative geometry, obtained with the help of the BENDM program (marked by the index n) is shown in table 2. The half-straight part of the coil block S from the magnet center was determined with the help of the Roxie program [11] in the process of optimization of the field quality for the dipole magnet.…”
Section: Minimization Of Lengths For the Coil Block Ends Of The Dipol...mentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison between designs of the old geometry [10] (marked by the index o) and the new alternative geometry, obtained with the help of the BENDM program (marked by the index n) is shown in table 2. The half-straight part of the coil block S from the magnet center was determined with the help of the Roxie program [11] in the process of optimization of the field quality for the dipole magnet.…”
Section: Minimization Of Lengths For the Coil Block Ends Of The Dipol...mentioning
confidence: 99%
“…For the coil block ends, modeled by the Roxie method as given using the table 2 values of the half-axis E n and angles β n , the maximal mechanical strain is |δ L| max = 0.44. For the old geometry of the dipole magnet [10] the maximal mechanical strain in the coil ends is |δ L| max = 0.73. Analytical comparison of the old and new geometry has shown that the introduced method of optimization gives a considerable opportunity to increase the effective length of the magnet, which follows from table 3.…”
Section: Minimization Of Lengths For the Coil Block Ends Of The Dipol...mentioning
confidence: 99%
“…The conceptual SIS 300 dipole design with design parameters was presented at ASC 2004 [2]. The final magnetic and mechanical design has been completed and will be presented [3]. The SIS 300 cable design parameters from ASC 2004 are presented in Table I.…”
mentioning
confidence: 99%